Effect of Melatonin in Broccoli Postharvest and Possible Melatonin Ingestion Level - Antonio Cano; Manuela Giraldo-Acosta; Sara García-Sánchez; Josefa Hernández-Ruiz; Marino B. Arnao (Plants, 2022)
The post-harvest stage of broccoli production requires cold storage to obtain enough days of shelf life. It has been proved that melatonin is useful as a post-harvest agent in fruits and vegetables, including broccoli. In this study, the broccoli heads treated with melatonin have a longer shelf life than the control samples, which was reflected in parameters such as fresh weight, hue angle (expresses color quality), and chlorophyll and carotenoid contents. Treatments with 100 μM melatonin for 15 or 30 min seem to be the most appropriate, extending the broccoli’s shelf life to almost 42 days, when it is normally around 4 weeks. In addition, a study on the possible impact that melatonin treatments in broccoli could have on melatonin intake in humans is presented. The levels of superficial melatonin, called washing or residual melatonin, are measured, showing the possible incidence in estimated blood melatonin levels. Our results suggest that post-harvest treatments with melatonin do not have to be a handicap from a nutritional point of view, but more research is needed.